2022
DOI: 10.1021/acsami.2c02047
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Thermoelectric Performance of Cu2GeSe3 via Isoelectronic (Ag, S)-co-substitution

Abstract: Recently, ternary Cu-based Cu-IV-Se (IV = Sb, Ge, and Sn) compounds have received extensive attention in the thermoelectric field. Compared with Cu-Sb-Se and Cu-Sn-Se, Cu-Ge-Se compounds have been less studied due to its poor Seebeck coefficient and high thermal conductivity. Here, the Cu 2 GeSe 3 material with high electrical conductivity was first prepared, and then, its effective mass was increased by doping with S, which led to the Seebeck coefficient of the doped sample being 1.93 times higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…7 Cu 2 GeS 3 stands out due to its high absorption coefficient, good electronic properties arising from its large carrier concentration and high carrier mobility, and a direct band gap of 1.5-1.6 eV, all of which are highly desirable for single-junction solar cell applications. 1,8,9 In addition to photovoltaic application, Cu 2 GeS 3 has also been explored due to its thermoelectric performance, 10 as an anode material for lithium-ion batteries 11 and as a photocatalyst for hydrogen evolution from water. 12 Considering the importance of Cu 2 GeS 3 , various approaches have been adopted for its preparation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Cu 2 GeS 3 stands out due to its high absorption coefficient, good electronic properties arising from its large carrier concentration and high carrier mobility, and a direct band gap of 1.5-1.6 eV, all of which are highly desirable for single-junction solar cell applications. 1,8,9 In addition to photovoltaic application, Cu 2 GeS 3 has also been explored due to its thermoelectric performance, 10 as an anode material for lithium-ion batteries 11 and as a photocatalyst for hydrogen evolution from water. 12 Considering the importance of Cu 2 GeS 3 , various approaches have been adopted for its preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we achieved two relatively high PF values of 8.66 μW cm −1 K −2 in the Cu 1.988 Bi 0.01 Zn 0.002 GeSe 3 sample and 7.22 μW cm −1 K −2 in the Cu 1.986 Bi 0.01 Zn 0.004 GeSe 3 sample at 723 K, which were increased by 135 and 113% compared with the pristine Cu 2 GeSe 3 , respectively. As can be seen in Figure 8b, the highest PF value of the (Bi, Zn) co-doped Cu 2 GeSe 3 substrate was even higher than those of previously reported In-, 38 Cudeficient, 30 Ni-, 19 Ag−S-, 29 Ag−In-, 20 and Ag−Ga-doped 18 Cu 2 GeSe 3 substrates with high PF values.…”
Section: Phase Composition Ofmentioning
confidence: 52%
“…At the same time, they μ enhanced from 15.4 ( x = 0) to 37.3 cm 2 V –1 s –1 ( x = 0.02) at room temperature. It is worth noting that the high n of the Cu 2 GeSe 3 substrate was associated with the vacancy of Ge. , According to σ = ne μ, the σ of the Cu 2– x Bi x GeSe 3 sample decreased, which was attributed to a decrease of n . Huang et al reported that the n value was obviously reduced from 6.5 × 10 19 cm –3 for pristine Cu 2 GeSe 3 to 1.97 × 10 19 cm –3 for Cu 2– x GeSe 3 sample at 300 K when x was increased to 0.1, and the decrease of n in the Cu 2– x GeSe 3 sample was originated from the increase of Cu vacancy .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In recent years, the copper germanium selenide, Cu 2 GeSe 3 compound and phases based on it, have been intensively studied as potential environmentally friendly thermoelectric and photovoltaic materials [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%